General flow characteristics in a compliant model of a carotid bifurcation - Giddens, Don P.; Jones, Steve A.; Anayiotos, Andreas (My University, 1992)
The flow dynamic characteristics of a compliant model of a human carotid bifurcation were investigated and compared with a rigid model of similar geometry [1,2]. Using Laser Doppler Velocimetry the flowfield was interrogated in two orthogonal planes at different locations along the axis of the internal carotid. The wall motion under physiologic pulsatile conditions was also simultaneously monitored. Complicated flow features such as helical structures and regions of reversed flow were analyzed. Negative velocity regions at the proximal axial locations were augmented temporally and spatially for the compliant model. Helical structures had different temporal characteristics and appeared more spread towards the centerline in the presence of a compliant wall.
Keywords: Hemodynamics; Blood-vessels; Laser Doppler velocimeter